PWE-016 Colorectal cancer screening colonoscopy – absent distal polyps in advanced proximal neoplasia. (17th June 2017) - Hussein, M; Patel, RN; Polak, L; Kumar, A; Samanta, S
Abstract : Introduction: The National Health Service Bowel Cancer Screening Programme (NHS BCSP) offers colonoscopy to people testing positive for Faecal Occult Blood Test (FOBT) after the age of 60. The UK Flexible Sigmoidoscopy Screening Trial (UKFSST) found a reduction in incidence and mortality associated with colorectal cancer 1 . This led to the introduction of 'Bowel scope screening', which offers a once-only flexible sigmoidoscopy to people in the UK after the age of 55. It remains unclear if proximal neoplasia is being missed in people undergoing flexible sigmoidoscopy. We aim to investigate the distributions of pathology within the BCSP at a busy district general hospital in London. Method: In 2015, 22, 539 FOBT kits were returned out of the 43 884 (51.4%) sent out in the boroughs of Barking, Havering and Redbridge (BHR). Of those returned, 398 (1.8%) tested positive. We collected data for the 326 patients who attended for colonoscopy at BHR University Hospitals (81.9%). Subgroup analyses included age, sex, histology, location of polyps, number of polyps, polyp size and therapies. Results: Mean age 67, Male 60.4%. Polyps were found in 199 patients (61%), 488 polyps found in total, mean number of polyps 2.5 (Range 1–14), mean size 7 mm (Range 1 mm - 60 mm); 49 (15%) hyperplastic, 156 (47.9%) adenomas and 16 (4.9%) adenocarcinoma. 201 patients underwent a therapeutic intervention; 163 (81.1%) hot snare polypectomy, 50 (24.9%) cold snare polypectomy. Patients with adenoma/carcinoma were older (67.6 vs. 66.5, p=0.02) but there was no difference in sex (Male 61.4% vs. 59.4%, p=0.49) when compared to those without adenoma/carcinoma. Of 172 patients with adenoma/carcinoma, 111 (64.5%) were proximal to the splenic flexure (SF). 5 out of 16 (31.2%) adenocarcinomas were proximal to SF and 2 (40%) of these patients had no polyps distal to the SF. Conclusion: Patients with adenomas/carcinomas are older and those with proximal adenomas/carcinomas have more polyps but are smaller in size. One in three adenocarcinomas picked up during colonoscopy would be out of reach of a flexible sigmoidoscopy. Furthermore, over one third of the proximal cancers did not have distal polyps. Reference: . Atkin W, Edwards R, Kralj-Hans I, Wooldrage K, Hart A, Northover J, et al. Once-only flexible sigmoidoscopy screening in prevention of colorectal cancer: a multicentre randomised controlled trial. The Lancet. 2010;375(9726):1624–1633. Disclosure of Interest: None Declared